Writing Queer Eastern European Worlds: Queer-feminist Literary and Activist Practices in Romania - Ugron, Nóra (Romania, 2025)
In this paper, I analyse the practices and writings of the queer-feminist literary circle Cenaclul X from Romania, arguing that they enact imaginations of possible transformative queer Eastern European worlds. In order to analyze these, I look at how hegemonic ideas of Eastern Europe were constructed by West(ern Europe) and trace possible directions to unsettle these imaginaries in literary-activist practices. I borrow the idea ‘queer as corrupt’ to present an Eastern European corrupt a/temporality that disturbs the hegemony of modern-colonial Time on imaginaries of Eastern Europe, and to present a corrupted version of Eastern European queerness, one that is not feeding into liberal respectability politics. To exemplify these, the paper engages in theory driven close reading on several fragments from the first two literary anthologies published by Cenaclul X: Adăposturi. Antologie queer [Shelters. Queer anthology, 2021] and Luminișuri. Antologie de literatură queer ecologică [Meadows/Clearings. Queer ecological anthology, 2022].